Biosorption of Synthetic Dye by Macrofungi - Lee, Kek Kin; Kristanti, Risky Ayu; Yulisa, Arma; Rubiyatno; Ningsih, Fitria; Syafrudin, Muhammad; Hernandes, Erika; Albescu, Mihaela (Tecno Scientifica Publishing, 2022)
This research project aimed to provide an environmentally friendly method for the decolorization and biosorption of synthetic dye by utilizing fungi as biosorbents. The study was carried out by first growing the fungi in solid medium and then using the fungi as biosorbent to absorb dye in aqueous solution. In the first stage, screening experiments were carried out among 5 different types of fungi, and Pleurotus ostreatus was determined to have the highest growth rate. The Pleurotus ostreatus was recultivated with Remazol Brilliant Blue R dye to determine its dye removal ability. Pleurotus ostreatus sp. exhibited vigorous dye decolorization in agar medium within 2 days. By carrying out batch analysis, 4 parameters were examined, which were the effect of pH, surfactant concentration (Tween 80), salinity concentration and dosage of biosorbent. The results showed that the maximum dye decolourization by Pleurotus ostreatus can be achieved through establishing an acidic condition of pH 2, addition of 0.1mL of Tween 80, 0mg/l of sodium chloride concentration, and dosage of 8 plugs. Lastly, the experimental data was found to fit the Jovanovic Isotherm the most. In conclusion, Pleurotus ostreatus is capable of decolourizing and adsorbing dye particles in the dye aqueous solution.